Governance of prepaid consumption in China's sports industry based on collaborative governance theory: theoretical framework, realistic dilemmas, and practical pathways - Jianuo Su; Jinsheng He (Frontiers in Sports and Active Living)
The rapid development of prepaid consumption in China's sports industry has been hindered by fundamental issues such as operators’ blind expansion, lack of transparency in business information, absence of standard contract texts, and inadequate consumer rights protection. These challenges have led to business closures, unfair contract terms, difficulties in card refunds and transfers, and the excessive issuance of long-term or lifetime prepaid cards. These problems severely damage the industry's integrity and impede its healthy and sustainable development. Currently, the governance of prepaid consumption in the sports industry faces several realistic dilemmas, including unclear collaborative regulatory and law enforcement responsibilities of the government, an urgent need to improve the legal framework, ineffective government regulatory tools, difficulties in ensuring the safety of prepaid funds, and limitations in the credit evaluation system. By introducing the concept of collaborative governance, new ideas and practical solutions are proposed to address these issues. The practical pathways for collaborative governance of prepaid consumption in the sports industry based on this concept include constructing a collaborative regulatory mechanism to solidify the foundation of collaborative governance, improving legal regulations to broaden collaborative relief channels, innovating government regulatory tools to build a collaborative regulatory platform; optimizing fund custody mechanisms to ensure the safety of prepaid funds; and enhancing the credit regulatory system to refine the credit reward and punishment mechanism.